2003
DOI: 10.2214/ajr.180.6.1801577
|View full text |Cite
|
Sign up to set email alerts
|

Added Benefit of Thoracic Aortography After Transarterial Embolization in Patients with Hemoptysis

Abstract: The inferior phrenic and intercostal arteries were often missed on routine transarterial embolization in patients with hemoptysis. Postembolization thoracic aortography is useful for monitoring the effectiveness of embolization and for improving the detection of arteries contributing to hemoptysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…These results suggest that multi-detector row helical CT angiography can help in the planning of a focused and efficient nonbronchial systemic artery embolization, as was recently reported with single-detector row CT (19). Consequently, thoracic aortography, an invasive procedure still recommended by many authors to improve the detection of arteries contributing to hemoptysis (30,31,(35)(36)(37), should be replaced with CT angiography. Similar conclusions can be drawn for the depiction of the abnormal systemic artery responsible for bronchial bleeding in patients with congenital anomalies of the lung.…”
Section: Discussionmentioning
confidence: 58%
“…These results suggest that multi-detector row helical CT angiography can help in the planning of a focused and efficient nonbronchial systemic artery embolization, as was recently reported with single-detector row CT (19). Consequently, thoracic aortography, an invasive procedure still recommended by many authors to improve the detection of arteries contributing to hemoptysis (30,31,(35)(36)(37), should be replaced with CT angiography. Similar conclusions can be drawn for the depiction of the abnormal systemic artery responsible for bronchial bleeding in patients with congenital anomalies of the lung.…”
Section: Discussionmentioning
confidence: 58%
“…In the subgroup of 26 patients referred for embolization, the anatomic information provided by CT angiograms guided successful catheterization and rapid embolization of ectopic and/or othotopic bronchial arteries in 21 patients, namely 81% of cases. From a practical standpoint, the noninvasive approach provided by CTA is expected to modify the recommendations for the angiographic procedures according to which thoracic aortography should be performed before [23] or after [24] bronchial artery embolization to identify all the systemic arterial supply to the bleeding site. Owing to the possibility to detect not only ectopic bronchial arteries, but also abnormal nonbronchial systemic arteries [10,25], CTA should contribute to the improvement of the immediate success rate of embolization whatever the underlying disease [26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have reported the occurrence of fistulous communication in the setting of hemoptysis[13] and ischemic coronary steal. [46] One case of hemoptysis has also been attributed to a fistula between a left bronchial artery and an internal mammary coronary artery bypass graft.…”
Section: Discussionmentioning
confidence: 99%